2013
DOI: 10.1371/journal.pone.0065281
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for the Detection of Neutralizing Antibodies against Mumps Virus

Abstract: Neutralization test is the most reliable method of evaluating immunity against viral diseases but there is no standard procedure for mumps virus, with tests differing in the infectivity of the challenge virus, 50% plaque reduction or complete inhibition of cytopathic effects (CPE), and usage of complement. A reliable, easy, and simple neutralization test for mumps virus was developed in this study. A recombinant mumps virus expressing GFP was generated as a challenge virus. Complement was added to the neutrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Several groups have found that insertion of ATUs at this site was relatively well tolerated and resulted in little to no viral attenuation [ 49 , 50 ]. However, ATUs have been inserted into several other locations within the paramyxovirus genome, including between genes N and P [ 51 ]; P and M [ 44 , 52 , 53 , 54 , 55 ]; M and F [ 52 ]; and H and L [ 56 , 57 ], which have resulted in varying levels of attenuation. Van Remmerden et al noted that insertion of an ATU encoding eGFP in the first gene position was attenuating, whereas insertion between the SH and G genes was not [ 58 ].…”
Section: Design Of Reporter Paramyxoviruses and Orthomyxovirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have found that insertion of ATUs at this site was relatively well tolerated and resulted in little to no viral attenuation [ 49 , 50 ]. However, ATUs have been inserted into several other locations within the paramyxovirus genome, including between genes N and P [ 51 ]; P and M [ 44 , 52 , 53 , 54 , 55 ]; M and F [ 52 ]; and H and L [ 56 , 57 ], which have resulted in varying levels of attenuation. Van Remmerden et al noted that insertion of an ATU encoding eGFP in the first gene position was attenuating, whereas insertion between the SH and G genes was not [ 58 ].…”
Section: Design Of Reporter Paramyxoviruses and Orthomyxovirusesmentioning
confidence: 99%
“…Neutralization assays have also been developed using bioluminescent reporter proteins, which can be automated to measure the reduction of virally-expressed luciferase [ 73 ]. Such assays have been developed for influenza viruses [ 61 , 74 ], in addition to several paramyxoviruses including measles virus [ 75 ], mumps virus [ 55 ], HMPV [ 54 ], and RSV [ 72 , 73 ].…”
Section: Applications Of Reporter Paramyxoviruses and Orthomyxovirmentioning
confidence: 99%
“…Acute infection with mumps virus is manifested by demonstrable swelling of the parotid glands and several complications including aseptic meningitis, encephalitis, deafness, orchitis, oophoritis, and pancreatitis. Generally, clinical diagnosis is based on parotid swelling [ 1 3 ]. Laboratory detection and diagnosis are based on isolation of the virus, detection of the viral gene, or serological confirmation (generally the presence of anti-mumps virus IgM antibodies).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for mumps virus, there is no standard procedure for easy detection of virus-infected cells and for evaluation of antiviral reagents. Furthermore, a period of more than 6 days after infection is required until appearances of an obvious CPE or plaque in many cases [ 3 , 6 – 8 ]. For laboratory confirmation and experimentation of mumps virus, it is useful if the method for detection of infected cells is easy, rapid, and independent of CPE and plaque formation.…”
Section: Introductionmentioning
confidence: 99%
“…There are no well-defined protective serological response threshold against mumps virus infection [1–4], and serological methods for detecting mumps antibodies have varying sensitivity and specificity [2]. Functional neutralizing antibody assays, such as the plaque reduction neutralization test (PRNT), are thought to provide the best estimate of protection [2], but there is no standard procedure for mumps virus infection [5].…”
mentioning
confidence: 99%